2010
DOI: 10.5114/aoms.2010.17083
|View full text |Cite
|
Sign up to set email alerts
|

Changes in attainment of lipid goals by general practitioners and specialists in patients at high cardiovascular risk in Hungary during 2004-2008

Abstract: IntroductionLipid-lowering therapy should achieve target levels. We assessed the change of the achievement of targets and the mean low-density lipoprotein cholesterol (LDL-C) levels in high-risk Hungarian patients.Material and methodsSix studies performed with patients of general practitioners (GPs) and specialists between 2004 and 2008 were evaluated: 9,508 patients from GPs and 2809 from specialist practices (total 12,317).ResultsDuring this 4-year period the LDL-C level decreased by 0.73 mmol/l and the LDL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…These findings are in general agreement with previous data from Hungary [8,9,12]. By comparison, data from the EUROASPIRE surveys among patients with CHD showed a substantial 51% reduction in raised TC levels (4.5 mmol/l) from 1995 to 2007.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in general agreement with previous data from Hungary [8,9,12]. By comparison, data from the EUROASPIRE surveys among patients with CHD showed a substantial 51% reduction in raised TC levels (4.5 mmol/l) from 1995 to 2007.…”
Section: Discussionsupporting
confidence: 93%
“…The authors also specified that the use of combination therapy (e.g. statin plus ezetimibe) contributed to better goal achievement [13,14]. This interpretation is in agreement with communitybased studies that showed a significantly improved outcome in lipid targets following the addition of ezetimibe to a statin [15][16][17].…”
Section: Lipidology Update 2011supporting
confidence: 69%
“…Also, much more attention needs to be paid to changing treatment of patients to achieve target levels. In one of the trials Mark et al reported a higher percentage of 12 317 high-risk patients achieving LDL-C targets when treated by specialists compared with those followed up by GPs (43% vs. 32%, respectively; p < 0.0001) [13,14]. The impact of this effect is likely to increase as more statins (and other lipid-lowering drugs) become generic.…”
Section: Lipidology Update 2011mentioning
confidence: 99%
“…At the end of the study the rate of achieving the 100 mg/dl LDL cholesterol target level was 58%, that of HDL cholesterol target level (40 mg/dl in males, 50 mg/dl in females) was 67% and in the case of triglyceride levels (150 mg/dl) 48%. The 58% in 100 mg/dl LDL cholesterol achievement rate is a very good result compared to that found in another observational study carried out in Hungary between 2004 and 2008, where among specialists the best result was 43% 4 . The 58% LDL cholesterol goal attainment in CORVUS is comparable to the results of the CEPHEUS study in which it varied between 40% and 68% in different European countries 5 .…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S mentioning
confidence: 45%